2018
DOI: 10.1038/nrdp.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum psychiatric disorders

Abstract: Pregnancy is a complex and vulnerable period that presents a number of challenges to women, including the development of postpartum psychiatric disorders (PPDs). These disorders can include postpartum depression and anxiety, which are relatively common, and the rare but more severe postpartum psychosis. In addition, other PPDs can include obsessive-compulsive disorder, post-traumatic stress disorder and eating disorders. The aetiology of PPDs is a complex interaction of psychological, social and biological fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
194
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(208 citation statements)
references
References 248 publications
(230 reference statements)
3
194
0
11
Order By: Relevance
“…2018). Risk factor screening may be conducted after symptom screening has occurred, or may be included in the development of screening tools which assess both symptoms and risk (Austin et al .…”
Section: Discussionmentioning
confidence: 99%
“…2018). Risk factor screening may be conducted after symptom screening has occurred, or may be included in the development of screening tools which assess both symptoms and risk (Austin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum depression (PPD) refers to a depressive episode with moderate‐to‐severe severity in four weeks after delivery (Segal, Marty, & Coolidge, 2017). Reviews have reported a prevalence of PPD in low‐income and middle‐income countries, ranging from 14% to 20%, higher than that in high‐income countries (Ding, Chen, & Di, 2014; Fisher et al., 2012; Meltzer‐Brody et al., 2018). More and more researches focused on PPD because PPD has adverse impacts both on new mothers and infants.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal depression (PND) is a debilitating disorder that occurs during pre‐ to postpartum transition with a prevalence of 19% . PND has long‐term detrimental effects on mother–infant bonding, infant wellbeing, and socio‐cognitive development and involves both genetic and environmental factors . Mechanisms related to sex‐steroid hormonal fluctuations and alterations in the serotonergic system have been suggested to underlie the pathobiology of PND.…”
Section: Introductionmentioning
confidence: 99%